A novel small motor measurement system based on ultrasonic bearings. (15th January 2021) - Pan, Song; Wang, Dong; Huang, Weiqing
Highlights: A new performance test system was developed based on novel ultrasonic bearing. The presented measurement system is simple and is easy to implement. The friction torque was reduced by up to 80% and the torque resolution is 0.1 mN.m. Compared with existing instrument, lower friction torque is realized. In the low-speed range, good speed stability is obtained. Abstract: A small torque measurement system has been developed based on two novel ultrasonic levitating bearings excited by piezoelectric vibrators. The modal analysis and harmonious response analysis are conducted to investigate its characteristics and driving parameters. Another problem of this application is to exert braking force on a rotating shaft. A noncontact eddy current loading system is designed and evaluated using Maxwell equations. To validate the friction reduction of ultrasonic bearing, a test system is established. The experiments show that with the presented ultrasonic bearing, the friction torque was reduced by up to a maximum of 80%. In addition, a small ultrasonic motor prototype was used to verify the presented system, and the experimental results show that it has realized torque test with precision of 0.1 mN.m. The comparison results with a commercial testing instruments have shown that the presented system has lower friction torque and has good low speed stability.